Cupping Therapy (حجامه) in the view of Islamic teaching - Khoso, Dr. Aijaz Ali; Hammad, Muhammad; Ahmed, Dr. Muneer (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
The term "cupping therapy" refers to treatments that involve applying sucking cups to specific skin regions for therapeutic reasons. Cupping therapy is a straightforward, risk-free, comfortable, efficient, cost-effective, and time-saving procedure. Traditional wet cupping therapy is a two-step process that involves cupping first, then superficially scarifying the skin (also known as the double S technique). Traditional wet cupping therapy was found to be successful in treating carpal tunnel syndrome in a German study. Al-hijamah is a three-step method that involves wet cupping therapy in prophetic medicine (suction, scarification, and suction technique, ie, triple S technique). According to the evidence-based Taibah mechanism, al-hijamah is a successful excretory therapy that purges the blood and interstitial spaces of harmful pathogenic chemicals. we firmly advocated Al-hijamah in our earlier articles for normal medical practice in hospitals. Al-hijamah was strongly advised for the treatment of thalassemia. In healthy people, al-hijamah dramatically reduced serum ferritin levels. Al-hijamah is an excretory procedure that considerably purges blood of harmful chemicals. Thalassemia may be a good candidate for treatment with Al-hijamah to remove extra iron and ferritin from thalassemic blood (via percutaneous iron excretion), as we mentioned in earlier papers. Al-hijamah is a brand-new percutaneous iron excretion therapy (PIET), which we will explore in this article. Interestingly, despite their distinct etiologies and pathophysiology, autoimmune disorders and migraine headaches responded favorably to al-hijamah treatment.